2019
DOI: 10.1016/j.ijpharm.2019.01.058
|View full text |Cite
|
Sign up to set email alerts
|

Type 1 Diabetes Mellitus reversal via implantation of magnetically purified microencapsulated pseudoislets

Abstract: Microencapsulation of pancreatic islets for the treatment of Type I Diabetes Mellitus (T1DM) generates a high quantity of empty microcapsules, resulting in high therapeutic graft volumes that can enhance the host's immune response. We report a 3D printed microfluidic magnetic sorting device for microcapsules purification with the objective to reduce the number of empty microcapsules prior transplantation. In this study, INS1E pseudoislets were microencapsulated within alginate (A) and alginate-poly-L-lysine-al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 47 publications
0
15
0
Order By: Relevance
“…Espona-Noguera et al followed a different approach in which IONP-loaded INS1E pseudoislets were encapsulated in alginate and alginate-poly-L-lysine-alginate (APA) microcapsules [ 582 ]. Prior to transplantation, removal of empty microcapsules by a microfluidic magnetic sorting device was performed to reduce transplant volume.…”
Section: Other Soft Tissue Regeneration and Engineeringmentioning
confidence: 99%
“…Espona-Noguera et al followed a different approach in which IONP-loaded INS1E pseudoislets were encapsulated in alginate and alginate-poly-L-lysine-alginate (APA) microcapsules [ 582 ]. Prior to transplantation, removal of empty microcapsules by a microfluidic magnetic sorting device was performed to reduce transplant volume.…”
Section: Other Soft Tissue Regeneration and Engineeringmentioning
confidence: 99%
“…In strategies such as microencapsulation, the volume of the transplanted islets is lower than the volume of the hydrogel material due to the possible presence of empty micro-capsules within the cell/capsule mix [131]. In this case, some hydrogels such as alginate, which is widely used for encapsulation procedures, can generate foreign body responses, amyloid formation, and fibrosis, leading to device failure [132,133]. Nanoencapsulation technology can be more beneficial as each capsule is fabricated according to the size and shape of an islet.…”
Section: Second Component Of the Tissue Engineering Strategy: Generation Of Supporting Cell-laden Scaffolds For Insulin-producing Cellsmentioning
confidence: 99%
“…The use of alginate-based microcapsules containing pancreatic islets in the T1DM treatment has shown great promise since many studies have shown the successful restoration of the blood glucose levels in diabetic animal models [64].…”
Section: Microencapsulationmentioning
confidence: 99%
“…In this regard, aiming to reduce the microcapsules graft volume, separation of microencapsulated islets from non-therapeutic microcapsules is usually accomplished by hand selection; however, the separation procedure is slow and tedious, thus complicating its reproducibility [77,78]. Recently, a novel microcapsule sorting system allows for the separation of magnetically labeled microencapsulated islets from empty microcapsules [64]. This purification system is based on a magnetic separation through a microfluidic device containing magnets, which guide the magnetized microencapsulated islets towards an output channel, while the empty microcapsules are eliminated through a different output channel.…”
Section: Microencapsulationmentioning
confidence: 99%